The Effectiveness of English Language Learning Among Elementary School Students - Ika Rahmani; Nabila Aura Yusra; Anisa Amelia; Fatimah Zuhra; Suci Isnaini Mauliza; Zuraini Zuraini (Journal of Education and Teaching Learning, 2026)
This study explores the effectiveness of English language learning among elementary school students at State Elementary School 20 Bireuen, Aceh, Indonesia. Effective English instruction at the elementary level is essential because it provides a strong foundation for students’ future language development and communication skills. This study aims to identify students’ learning experiences, teaching practices, and the factors influencing the effectiveness of English language learning. A qualitative descriptive approach was employed. Data were collected through classroom observations, questionnaires, and documentation involving 100 fifth- and sixth-grade students. The findings indicate that English language learning is generally effective, as reflected in students’ positive attitudes, active participation, and satisfactory understanding of the learning materials. Approximately 75% of students expressed a high interest in learning English, while 68% reported that they understood the lessons delivered by the teacher. Interactive teaching methods, including games, group discussions, and the use of visual media, were found to enhance students’ engagement and motivation. However, some students continued to experience difficulties, particularly in grammar and vocabulary, indicating the need for more individualized instructional support. In addition, teacher creativity, student motivation, and support from the home environment emerged as important factors influencing learning effectiveness. The findings suggest that implementing interactive teaching strategies and strengthening collaboration between schools and families can improve the quality of English language learning at the elementary school level.